Teachers’ understanding and experiences in the teaching of oral Communication at ordinary level with reference to Sadza cluster in Chikomba district - Mutara, Charity (Midlands State University, 2017)
The purpose of this study was to investigate the teachers’ understanding and experiences in the teaching of oral communication in English at O’ Level in Sadza Cluster in Chikomba District. The study was necessitated by the need to know the teachers’ understanding and experiences in the teaching of oral communication in English. A qualitative research design premised on phenomenology was used for it enabled the researcher to get current and on the ground information of teachers’ understanding and experiences in the teaching of oral communication at O’ Level. The population comprised of all English teacher from each of the 7 schools in Sadza Cluster. Purposive sampling was used to select English teachers who were interviewed. All the seven teachers participated in this study by answering interview question. The researcher used interview guides and biographical data to collect data from the teachers. The study revealed that pupils need to be exposed to resource materials and engaged in interactive activities to enhance their oral proficiency. The teachers acknowledged that they rarely concentrated on the teaching of oral communication as it was no tested or examined at O’ Level. Teachers were using structural teaching methods as they wanted to enhance pupils’ writing skills in preparation for the final written examination, thereby ignoring oral skills. The researcher thus recommended that the curriculum should include oral tests at O’ Level and that teachers should be eclectic in their selection of teaching method in order to produce students who have both oral and written English proficiency. The researcher also recommended that pupils should be taught oral communication starting at lower levels.